Exploring the interface between the decolonisation of higher education and open access - Radebe, Khawulile Ednah (Department of Knowledge and Information Stewardship, 2023)
This study aims to investigate the similarities between decolonisation in higher education and Open Access (OA). This study was motivated by South African students united under the #FMF (#FeesMustFall) movement who revolted against colonised higher education system, restricted access to higher education, colonised curriculum, outsourcing, and higher education fee increases. Students held enraged protests against the government system, citing the little development in universities in the two decades since South Africa became a constitutionally free and democratic country. The researcher aims to find ways in which OA can contribute to solving some of the issues that were brought forward during the #FMF protests. This qualitative study is situated in a transformative research paradigm. The challenges in OA and OA publishing identified in the literature review and informed by social justice theory were used as guidelines to formulate appropriate research questions. Data was collected using snowball sampling from the #FMF activists, staff and students from three South African universities, namely: Rhodes University, University of Cape Town (UCT) and Nelson Mandela university. Findings show that there are definite similarities between the objectives of OA and #FMF movements, however neither movement was readily aware of similarities, thus there has been no open communication between the stakeholders of the movements to engage and support one another in fulfilling their mutual objectives.